Metallothermic Production of Aluminum-Strontium Master Alloy for Modification of Silicon - Sezer, Rasit; Hizli, Goksel; Bilen, Aysegul; Erturk, Selim; Dispinar, Derya; Arslan, Cuneyt (SPRINGER, 2020)
Strontium master alloy is widely used in today's aluminum foundries for modification of Al-Si alloys. In this study, Al-Sr master alloy was produced in molten Al alloy directly from strontium carbonate instead of using the pure strontium metal which is difficult to store in the air due to its high oxygen affinity. In a laboratory-scale induction furnace, SrCO3 and SrO powders were injected into the liquid metal via argon flow and subjected to reduction reaction. The oxygen-free medium required for the reduction was provided by the gas purged on both the surface and the inside of the liquid metal. Hence, the master alloy was produced directly by an economical process. Moreover, the addition of Mg to the reducing melt decreased the surface tension of the liquid aluminum; as a result, the reduction efficiency was increased. At the best of the results, the master alloy containing 5.15% Sr was obtained by reducing approximately half of the fed SrO by Al6Mg. This master alloy was used to modify A360 alloy, and the same modification effect as the commercial Al5Sr master alloy was observed.
Keywords: Al-Sr master alloy; Silicon modification; Metallothermic reduction; Aluminothermy; EFFICIENT GRAIN REFINER; SURFACE-TENSION; LIQUID ALUMINUM; PURE ALUMINUM; SR ALLOY; ELECTROLYSIS; MICROSTRUCTURES; PERFORMANCE; DISSOLUTION; EXTRACTION; Metallurgy & Metallurgical Engineering